1962
DOI: 10.1111/j.1469-1809.1962.tb01523.x
|View full text |Cite
|
Sign up to set email alerts
|

Haptoglobin and transferrin variation in humans and primates: two new transferrins in Chinese and Japanese populations

Abstract: Summary1. Haptoglobin and transferrin gene frequencies have been determined for Chinese, Japanese, New York City Negro, Sapelo Negro, and Eskimo populations.2. A genetically determined transferrin variant DChi was observed in 6 % of the individuals in the Chinese population. This previously undescribed transferrin migrated slightly more rapidly in starch gel electrophoresis than the transferrin D1 of New York City Negroes.3. A new transferrin variant B3 was observed in a Japanese family. The mobility of this t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

4
15
0

Year Published

1963
1963
1986
1986

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 64 publications
(19 citation statements)
references
References 44 publications
4
15
0
Order By: Relevance
“…17.8% of the Piaroa Indians we studied; a variant with similar mobility was observed in 58% of 91 Yupa Indians from the extreme west of Venezuela (19). The original demonstration of a variant with this mobility was in people of Chinese extraction (Kwantung Province, southern China) residing in New York City (20). It is impossible to state at present whether these are identical variants.…”
mentioning
confidence: 86%
“…17.8% of the Piaroa Indians we studied; a variant with similar mobility was observed in 58% of 91 Yupa Indians from the extreme west of Venezuela (19). The original demonstration of a variant with this mobility was in people of Chinese extraction (Kwantung Province, southern China) residing in New York City (20). It is impossible to state at present whether these are identical variants.…”
mentioning
confidence: 86%
“…In Japanese populations, Parker and Bearn (1961), Matsumoto (1964), Omoto and Harada (1972), and Kirk et al (1978) have reported rare electrophoretic variants. Ferrell et al (1977), examining 4,029 Japanese residing in Hiroshima and Nagasaki, reported three types of B-variant and five types of D-variant.…”
Section: Introductionmentioning
confidence: 99%
“…The B1 variant was first described in England by Harris et al (1958) and the identification of the Japanese variants as B1 is almost certainly incorrect, a point which will be discussed in greater detail below. The B3 had been described in a Japanese from Ube by Parker and Bearn (1961).…”
Section: Introductionmentioning
confidence: 99%